2017
DOI: 10.1002/2016ja023506
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the development of double‐peak subauroral ion drift (DSAID)

Abstract: This study focuses on the newly described ionospheric feature, called double‐peak subauroral ion drift (DSAID), which is a subclass of the well‐known single‐peak SAID. Double‐layer Region 2 (R2) field aligned currents (FACs) could be the main driver of DSAID. Our aim is to gain new insights into the development of DSAID during its two‐stage progression. Observational results are provided by five scenarios, each demonstrating a certain progression sequence of DSAID. Results show that SAID/DSAID occurred during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
1
12
0
1
Order By: Relevance
“…The magnetospheric driving source of double-peak subauroral ion drifts: Double ring current pressure peaks. Geophysical Research Letters,46,[7079][7080][7081][7082][7083][7084][7085][7086][7087] of the two velocity peaks could be either comparable to each other or significantly different (He et al, 2016;Horvath & Lovell, 2017;Wei et al, 2019). Both of the two flow peaks are typically accompanied with two upward flow peaks and two ion temperature peaks.…”
Section: Citationmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetospheric driving source of double-peak subauroral ion drifts: Double ring current pressure peaks. Geophysical Research Letters,46,[7079][7080][7081][7082][7083][7084][7085][7086][7087] of the two velocity peaks could be either comparable to each other or significantly different (He et al, 2016;Horvath & Lovell, 2017;Wei et al, 2019). Both of the two flow peaks are typically accompanied with two upward flow peaks and two ion temperature peaks.…”
Section: Citationmentioning
confidence: 99%
“…Recently, a newly recognized phenomenon called double-peak subauroral ion drifts (DSAIDs) is categorized as a subset of SAPS (He et al, 2016). Observational results showed that DSAIDs appear as sunward drift with two velocity peaks in the subauroral midlatitude trough region in limited MLT sectors, and the magnitude of the two velocity peaks could be either comparable to each other or significantly different (He et al, 2016;Horvath & Lovell, 2017;Wei et al, 2019). Both of the two flow peaks are typically accompanied with two upward flow peaks and two ion temperature peaks.…”
Section: Introductionmentioning
confidence: 99%
“…Before reports of the SAPS from radar measurements, the poleward electric field was found in satellite measurements (Smiddy et al 1977;Maynard 1978;Spiro et al 1979;Rich et al 1980). Later improvement of the sensor sensitivity enabled measurements of the fine structure in the latitudinal pattern of the electric field (Erickson et al 2016;Horvath and Lovell 2017). Horvath and Lovell (2017) found doublepeak subauroral ion drift (DSAID) in measurements performed with the Defense Meteorological Satellite Program (DMSP) when it flew across the ionospheric trough at an approximately 840-km altitude.…”
Section: Introductionmentioning
confidence: 99%
“…Several magnetic factors are also found to be related to SAPS such as Kp, Dst, IMF, cross polar cap potential, conductance, electrojet, and zonal wind as shown in many reports (e.g., Aa et al., 2020; Foster & Vo, 2002; Huang & Foster, 2007; Kunduri et al., 2017; Wang et al., 2008, 2011; Zheng et al., 2008). Besides, SAPS are divided into several types because of the morphological features, such as double subauroral ion drifts (DSAID) and abnormal subauroral ion drifts/abnormal subauroral polarization drifts that are different in their formation mechanisms (Ebihara et al., 2008; He et al., 2014, 2016; Horvath & Lovell, 2017, 2018; Liléo et al., 2010; Voiculescu & Roth, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…. Besides, SAPS are divided into several types because of the morphological features, such as double subauroral ion drifts (DSAID) and abnormal subauroral ion drifts/abnormal subauroral polarization drifts that are different in their formation mechanisms (Ebihara et al, 2008;He et al, 2014He et al, , 2016Horvath & Lovell, 2017Liléo et al, 2010;Voiculescu & Roth, 2008).…”
mentioning
confidence: 99%